Réponses

2014-10-10T15:38:13+02:00
C= (2-12)/(2-12)=1
D= (15+(-3)(-2)+5)/(-2)(-7)-(-6+8(-3))=(15+6+5)/(14-24)=26/-12=-26/10
2014-10-10T15:38:19+02:00
Calculer les expressions suivantes en détaillant les étapes de calcul :
C = (- 1) x (- 2) - (- 3) x 4
          -----------------
        2 - 2 x - (- 6)
C = 2 + 12
      2 + 12
C = 14/14
C = 1

D = 15 + [(- 3) x ((- 2) + (- 5)]
            ----------------------
      - 2 x - 7 - [(- 6) + 8 x (- 3)]
D = 15  + (6 - 5)
       - 2 x 7 - (- 6 - 24)
D = 15 + 1
     - 14 + 30
D = 16/16
D = 1